Evaluation the role of Aggregatibacter Actinomycetemcomitans on IL-18 Production in Periodontitis Patients (Texas Journal of Medical Science, 2022)
Background: Aggregatibacter actinomycetemcomitans one of the most common periodontal pathogen with direct effect on periodontium, this bacterium possesses many virulence characteristics that allow it to colonize the oral cavity, invade, and evade the host's immune system. periodontitis is chronic multifactorial disease and cytokines can signal and amplify the immune responses during infection IL-18 has a role in in the body's inflammatory and immune responses in the body, it plays an essential role as a chemotactic factor for the attraction of neutrophils and lymphocytes and its expression has been reported to increase in chronically inflamed periodontal tissues.Aim of study: This study was conducted to investigate the role of Aggregatibacter actinomyctecomtans in pathogeneses of periodontitis and their effect on serum level of IL-18 in periodontitis patient and compare with control group.Materials and Methods: fifty-five subjects were enrolled in this case control study, their age range (23-55) years. They were 30 periodontitis and 25 healthy controls group. Sub-gingival plaque samples were collected from four deepest periodontal pockets in each subject of patients group and gingival sulcus in control group. Detection of Aggregatibacter actinomyctecomtans performed by means of RT-PCR, whereas ELISA was used to evaluate the level of IL-18.Results: The study results revealed statically no significant differences in quantity of Aggregatibacter actinomyctecomtans and IL-18 levels between patients and controls. Moreover, there is no correlation between Aggregatibacter actinomyctecomtans and the IL-18Conclusion: The lack of correlation between Aggregatibacter actinomyctecomtans and the IL-18 indicates that its activation is associated   with inflammatory processes that are induced by a number of external factors, other than bacteria.